INTEGRASI STRUKTUR DAN FUNGSI BAGIAN TUMBUHAN DENGAN BAYANI, BURHANI, ‘IRFANI DI SDIT BUNAYYA - Asriana Harahap; Syarifuddin Harahap (DIRASATUL IBTIDAIYAH, 2021)
AbstractPlants are living things that do not experience the activity of moving like humans and animals, but they can reproduce in their own way. The parts that are in plants are always different from one another, this is influenced by climatic factors and geographic areas. Areas that have lots of sunlight will be different from plants that live in areas with cool weather or below 20 degrees Celsius. Based on the issues that have developed in education during this decade, this paper will try to develop science material on "Structure and Function of Plant Parts" in SDIT Bunayya students. If the main source (origin) of science in the Bayani approach is text (revelation), then in the 'irfani approach the main source is experience (experience), which is an authentic life experience, and is actually an invaluable lesson. Inner experiences that are very deep, authentic, innate, and almost unspeakable by logic and cannot be expressed by language. This is what is called direct experience, and is called hudhri science in the isyraqiyyah tradition. All these authentic experiences can be felt directly without having to say it first through the expression of "language" or "logic". Keywords: integration; plants; bayani; burhani; and 'irfani.